Cerebral pyogranulomatous encephalitis caused by Cladophialophora bantiana in a 15-week-old domestic shorthair kitten. Issue 2 (November 2016) - Russell, Elise B; Gunew, Marcus N; Dennis, Michelle M; Halliday, Catriona L
Case summary: A case of cerebral phaeohyphomycosis caused by Cladophialophora bantiana is described in a 15-week-old domestic shorthair kitten. Relevance and novel information: Cerebral phaeohyphomycosis is a rare condition in cats caused by dematiaceous fungi. This report describes the clinical and histopathological findings in the youngest case documented in a feline, provides a brief review of aetiology, diagnosis, treatment and prognosis of cerebral phaeohyphomycosis and demonstrates the importance of molecular diagnostics in accurate mycotic species identification.